The Role of Pores in the Cavitation Erosion of Additively Manufactured Metal: An In Situ Study - Yuan Song; Zhenhua Wang; Bingyang Ma (Metals)
Additively manufactured (AM) parts have been applied in many areas with the risk of cavitation erosion (CE), and pores are common defects in AM metals. However, the role of pores in CE is still unclear, and a systematic investigation is needed. In this study, 316L stainless steel was selected as a model material and produced using laser powder bed fusion; the porosity was 6.4%. The morphological evolution of various pores during CE was investigated via electron backscatter diffraction and scanning electron microscopy. It was found that material removal easily occurred around large polygonal pores. The critical size for large polygonal pores was estimated to be between 13 and 20 μm. For narrow pores, concavity first appeared around the pores during CE, and then the narrow pores closed. Small spherical pores with sizes of 3–9 μm showed strong resistance to CE, and no damage occurred within the 60 min CE period. The main reason that different pores played different roles in CE was analyzed. Finally, factors for improving the CE resistance of AM metals were suggested. The research results are helpful for understanding the CE behaviors of AM metals and porous materials.